Statistique, géographie et savoirs sur l’espace en Allemagne (1780-1820) - Guillaume Garner (Cybergeo, 2008)
At the end of the 18th century in Germany, statistics and political geography as fields of knowledge were still very similar, particularly because their space approach is centered on the state territory and hence emphasizes the importance of political boundaries in the definition of their subjects. The wars during the revolutionary and imperial era, while disrupting the political map of Europe and of the Holy Empire, made such an approach less and less operative. In the beginning of the 19th century, geographers therefore claimed their intention to investigate territories which were delimited by natural boundaries, while the traditional statistics had many difficulties to elaborate a new methodological framework. After 1815 the stabilization of the political situation in Europe lead to a revival of political geography which was partly based on a « inveigling of the inheritance » of the statistics whose social and scientific legitimacy was weakened. In the same time, the administrative quantifying statistics became established, as the Prussian example shows, and developed its own approach and knowledge of space.